Gut microbiota: a crucial player in the combat against tuberculosis - Lin, Jie; Chen, Dongli; Yan, Yongen; Pi, Jiang; Xu, Junfa; Chen, Lingming; Zheng, Biying (Frontiers in Immunology, 2024)
The mammalian gastrointestinal tract quickly becomes densely populated with foreign microorganisms shortly after birth, thereby establishing a lifelong presence of a microbial community. These commensal gut microbiota serves various functions, such as providing nutrients, processing ingested compounds, maintaining gut homeostasis, and shaping the intestinal structure in the host. Dysbiosis, which is characterized by an imbalance in the microbial community, is closely linked to numerous human ailments and has recently emerged as a key factor in health prognosis. Tuberculosis (TB), a highly contagious and potentially fatal disease, presents a pressing need for improved methods of prevention, diagnosis, and treatment strategies. Thus, we aim to explore the latest developments on how the host's immune defenses, inflammatory responses, metabolic pathways, and nutritional status collectively impact the host's susceptibility to or resilience against Mycobacterium tuberculosis infection. The review addresses how the fluctuations in the gut microbiota not only affect the equilibrium of these physiological processes but also indirectly influence the host's capacity to resist M. tuberculosis. This work highlights the central role of the gut microbiota in the host-microbe interactions and provides novel insights for the advancement of preventative and therapeutic approaches against tuberculosis.